Employee Trust Betrayal and Fraud Dynamics in Indonesia’s Logistic Industry - Elok Nurindah Sari; Indrianawati Usman (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Fraud remains a persistent challenge for organizations in Indonesia, particularly within the logistics industry, which is characterized by complex operations and a high reliance on trust among parties. This study aims to identify the dynamics of employee trust betrayal and patterns of fraudulent behavior in Indonesian organizations. Employing an exploratory case study approach, the research analyzed internal corporate documents, including investigation reports, disciplinary records, and compliance policies from logistics sectors. The findings reveal a rising trend in fraud cases from 2019 to 2024, strongly linked to post-pandemic economic pressures, weak internal controls, and moral rationalization by offenders. Demographic analysis indicates that most perpetrators are early-career male employees under special contract status, suggesting a correlation between employment instability and unethical conduct. Theoretically, this study contributes to the literature by integrating Agency Theory and Fraud Triangle Theory to explain the behavioral roots of organizational fraud. Practically, it underscores the importance of integrity-based governance, multilayered monitoring, and an ethical culture that prioritizes accountability and transparency.